2019
DOI: 10.1016/j.memsci.2019.117252
|View full text |Cite
|
Sign up to set email alerts
|

Propylene - propane separation using Zeolitic-Imidazolate Framework (ZIF-8) membranes: Process techno-commercial evaluation

Abstract: Several recent studies investigated the use of the novel Zeolitic-Imidazolate Framework (ZIF-8) membranes for olefinparaffin separation. In this manuscript, a techno-commercial model is developed to examine the use of these membranes for separating propylene from propane. Single-stage and two-stage membrane processes were assessed for their performance compared to distillation. The assessment was conducted considering 70 wt% propylene feed, typically produced from the upstream depropanizer. The single-stage pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…The U-Z00 had maximum DCA (104.5°) for the hydrophobic properties of PVDF itself. 40 The hydrophilicity of PVP made the UP-Z00 has the lowest DCA (60°). With adding the three kinds of ZIF-8, The hydrophobicity of ZIF-8 led to the DCA of the MMM’s surface was increased.…”
Section: Resultsmentioning
confidence: 99%
“…The U-Z00 had maximum DCA (104.5°) for the hydrophobic properties of PVDF itself. 40 The hydrophilicity of PVP made the UP-Z00 has the lowest DCA (60°). With adding the three kinds of ZIF-8, The hydrophobicity of ZIF-8 led to the DCA of the MMM’s surface was increased.…”
Section: Resultsmentioning
confidence: 99%
“…Membranes with framework structures, particularly those composed of ZIF‐8, have attracted the most attention. [ 132 ] In 2011, Pan et al. first reported that ZIF‐8 membrane could sharply separate ethylene/propylene and ethane/propane gas pairs.…”
Section: Membrane Application In Olefin/paraffin Separationsmentioning
confidence: 99%
“…[ 3,8 ] High‐crystallinity MOF membranes have been widely used for difficult separations, especially for olefin/paraffin separations. [ 9–11 ] However, only very few ultrathin MOF membranes have been successfully obtained, mainly by the deposition of metal salts, ligands, or 2D MOF nanosheets or by electric fields onto inflexible inorganic supports or metal surfaces. [ 3,10,12 ] These membranes do not typically display high permeance and high selectivity simultaneously.…”
Section: Figurementioning
confidence: 99%
“…[ 13 ] Thus fabricating high‐performance membranes on flexible polymeric supports, especially those with high permeance, is crucial for realizing large‐scale applications of gas separation membranes. [ 11,13 ]…”
Section: Figurementioning
confidence: 99%